J'Accuse! Antisemitism and Financial Markets in the Time of the Dreyfus Affair - Quoc-Anh Do; Roberto Galbiati; Benjamin Marx; Miguel A. Ortiz-Serrano (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the stock market performance of firms with Jewish board members during the "Dreyfus Affair" in 19th century France. In a context of widespread latent antisemitism, initial accusations made against the Jewish officer Alfred Dreyfus led to short-lived abnormal negative returns for Jewish-connected firms. However, investors betting on these firms earned higher returns during the period corresponding to Dreyfus' rehabilitation, starting with the publication of the famous op-ed J'Accuse! in 1898. Our conceptual framework illustrates how diminishing antisemitic biases among investors might plausibly explain these effects. Our paper provides novel insights on how antisemitism can increase and decrease over short periods of time at the highest socio-economic levels in response to certain events, which in turn can affect firm value in financial markets.
Keywords: J15; J71; N23; G14; G41; 330; antisemitism; financial markets; discrimination